2019
DOI: 10.1097/fjc.0000000000000632
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Loading Doses With P2Y12-Receptor Antagonists in Patients Without Dual Antiplatelet Therapy Undergoing Elective Coronary Intervention

Abstract: Background: European Guidelines on Myocardial Revascularization recommend clopidogrel loading dose added to acetylsalicylic acid in elective percutaneous coronary interventions (PCIs). However, there is few evidence supporting this recommendation and other P2Y12 inhibitors have not been tested in these patients. Purpose: To evaluate the effectiveness and safety of different loading doses of clopidogrel and ticagrelor in patients without double antiplate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Aggregometry studies have shown that prasugrel and ticagrelor have stronger antiplatelet effects than clopidogrel; however, the net clinical benefits of these new antiplatelet drugs in patients with SCAD (which may reduce ischemic events but not significantly increase bleeding ) have not yet been confirmed 40) . In addition, ticagrelor is used in patients with SCAD who receive PCI, and its use is increasing, especially in high-risk diabetic patients or in complex coronary artery disease 41) . This real-world study will provide important insight into the efficacy and safety of ticagrelor in patients with SCAD.…”
Section: Safety Endpointsmentioning
confidence: 99%
“…Aggregometry studies have shown that prasugrel and ticagrelor have stronger antiplatelet effects than clopidogrel; however, the net clinical benefits of these new antiplatelet drugs in patients with SCAD (which may reduce ischemic events but not significantly increase bleeding ) have not yet been confirmed 40) . In addition, ticagrelor is used in patients with SCAD who receive PCI, and its use is increasing, especially in high-risk diabetic patients or in complex coronary artery disease 41) . This real-world study will provide important insight into the efficacy and safety of ticagrelor in patients with SCAD.…”
Section: Safety Endpointsmentioning
confidence: 99%
“…However, it also suggested that the administration of 600 mg LD of clopidogrel is associated with a lower risk of MACE [38]. This observation is further supported by a retrospective study of patients with stable coronary artery disease which shows no difference between different LD groups in terms of major bleeding and hemoglobin drop post PCI (39).…”
Section: Discussionmentioning
confidence: 77%
“…Recently, a retrospective study showed that a loading dose of ticagrelor resulted in lower post-procedural myocardial injury with lesser bleeding complications among European patients with stable coronary disease undergoing elective PCI. 14 As we have mentioned above, previous studies have found that ticagrelor reduced myocardial injury or long-term adverse cardiovascular events after PCI. However, to the best of our knowledge, there was no randomized prospective study designed to compare ticagrelor versus clopidogrel in preventing PCI-related PMI among patients with ACS.…”
Section: Discussionmentioning
confidence: 81%
“…Recently, a retrospective study showed that a loading dose of ticagrelor resulted in lower post-procedural myocardial injury with lesser bleeding complications among European patients with stable coronary disease undergoing elective PCI. 14…”
Section: Discussionmentioning
confidence: 99%